La secuencia didáctica como estrategia metodológica para fortalecer los procesos de enseñanza -aprendizaje del concepto de número entero en la Institución (2023)
The present investigation is carried out at the Educational Institution , with the objective of strengthening the concept of whole number, based on a didactic sequence focused on solving problem situations by strengthening numerical thinking. Due to the difficulties presented by the teachers when finding a didactic sequence that would allow the approach to the whole number concept and its acquisition of the concept by students. The teaching of mathematics is a process that grows every day, this process is significant when the context of the students is taken into account. According to Arteaga (2017) "Numerical thinking is defined as the ability to use numbers and numerical relationships to describe, interpret and predict situations, to solve problems in mathematical and non-mathematical contexts". Most students have difficulty relating concepts and operations, it is necessary to strengthen and use the whole number in problem situations that allow strengthening and building learning, using the didactic sequence as a strategy to achieve more effective learning, which students will improve their performance. The didactic sequence will be carried out in 10 sections, each of one hour of class, this activity will allow the observation of previous skills and knowledge. Through direct observation, the diagnostic test, the didactic sequence and the final test, it is possible to collect data and thus achieve the competencies. As techniques for data collection, observation was initially used, then a diagnostic test, a didactic sequence and a final test. The analysis of the results made it possible to show that the intervention generated significant changes in the group of students in relation to numerical thinking, it should be noted that the entire process and intervention from observation to the final test were important to achieve competencies in students.